The effect of interventions based on transtheoretical modelling on computer operators’ postural habits - Zeidi, Isa Mohammadi; Morshedi, Hadi; Zeidi, Banafsheh Mohammadi (Clinical Chiropractic, 2011)
Summary: Objective: To determine the effectiveness of ergonomic training on postural habits and computer operators’ psychosocial mediating variables based on the transtheoretical model (TTM). Design: A prospective randomized controlled trial. Setting: Departments of two universities in Qazvin, Iran. Participants: One hundred and thirty-four of operators, mean age 31.0±7.2 years, who worked at a computer for a minimum of 20h per week. The subjects were divided into intervention (n =67) and control (n =67) groups. Intervention: The intervention group received a TTM-based intervention involving eight 2-h sessions, which included 45–60min stage-matched ergonomic counseling, ergonomic behavior training, and a package of training materials comprising a facilitator''s handbook and a handout regarding computer ergonomic guidelines (Ergo-Guidelines). Outcome measures: Ergonomic knowledge, stage of change, self-efficacy, pros and cons, preventive behavior and rapid upper limb assessment (RULA) scores were measured at baseline, 3- and 6-month post-ergonomics training. Results: Although both groups were homogeneous in all variables at baseline, the intervention group showed significant improvements in stages of change (P <0.001), ergonomic knowledge (P <0.001), pros (P <0.05), cons (P <0.05) and self-efficacy (P <0.05). A significant decrease in RULA score was observed for the intervention groups; however, intervention did not significantly improve RULA. Conclusions: Results from this study provide evidence that TTM-based ergonomic training among computer operators can improve postural risk factors for musculoskeletal disorders (MSDs).